SELF DISCLOSURE DENGAN RESILIENSI PADA REMAJA DENGAN ORANG TUA TUNGGAL - Mika Oktaviana; Wahyuni Kristinawati (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2022)
This negative view of oneself and feelings if worthless in this single parent family teeneger will an impact on the development of their resilience. An important factor that influences resilience is self-concept. Self-concept is a part of personality that gives to rise to several behaviors that affect one’s thought processes, feelings, desires values and life goals. In addition to self-concept, there are also other factors, namely self-disclosure. Ko and Pu (2011) state that self-disclosure has a relationship with the level of resilience. This study uses quantitative research methods to determine the relationship between self-disclosure and resilience in single-parent adolescents with a number of respondents as many as 50 adolescents aged 14 – 18 years. Based on the result of the Pearson correlations test of 0.667 with (p>0.05) it can be said that theree is no positive relationship between resilience and self-disclosure